AERONAUTICAL FIXED TELECOMMUNICATION NETWORK: KOMUNIKASI PERALATAN AUTOMATIC MESSAGE SWITCHING CENTER - Mardiansyah Mardiansyah; Insani Abdi Bangsa; Ulinnuha Latifa; Rahmat Hidayat (LPPM STMIK Lombok, 2021)
Abstract Automatic Message Switching Center (AMSC) is a data communication control device or telex in a computer-based news distribution system that works in a store and forward manner, news that comes into AMSC is stored and then distributed according to the intended address. This system is available used for air traffic safety so that flights are carried out regularly, efficiently and economically. In addition, the AFTN network also functions to exchange news from or between BMKG offices (Meteorology and Geophysics Agency), Notic To Airman (NOTAM), Rescue Command Center (RCC) within certain boundaries between airline company offices as well as sending flight data, weather news and other related to the world of aviation. This practice is carried out at PERUM LPPNPI Air Navigation and Surveillance Equipment Husen Sastranegara Airport Bandung. As a result, at Bandung's Husein Sastranegara International Airport, using Automatic Message Switching Center (AMSC) as a tool for collecting flight information and Aeoronotical Fixed Network (AFTN) which processes all flight data. AFTN is a network system at AMSC that is used for flight data communication between one airport and another by using the address of each airport, both in Indonesia and in other countries in the world. And also Bandung itself is a Subcentre Station which has a WICC address. Abstrak Automatic Message Switching Centre (AMSC) merupakan suatu alat pengendali komunikasi data atau telex dalam sistem pengatur penyaluran berita berbasis komputer yang bekerja secara store and forward, artinya berita yang masuk ke AMSC disimpan lalu disalurkan sesuai dengan address (alamat) yang dituju. Tersedianya sistem ini di gunakan untuk keselamatan lalu lintas udara agar terselenggaranya penerbangan secara teratur, efisien, dan ekonomis. Selain itu, dengan adanya jaringan AFTN juga berfungsi untuk pertukaran berita dari atau antara kantor-kantor BMKG (Badan Meteorologi dan Geofisika), Notic To Airman (NOTAM),Rescue Command Center (RCC) dalam batas-batas tertentu antara kantor perusahaan penerbangan serta mengirimkan data penerbangan, berita cuaca dan berita lain yang berhubungan dengan dunia penerbangan. Praktek ini dilakukan di PERUM LPPNPI Air Navigation and Surveillance Equipment Bandara Husen Sastranegara Bandung. Hasilnya, Pada Bandara International Husein Sastranegara Bandung alat komunikasi yang digunakan yaitu: Automatic Message Switching Centre (AMSC) sebagai alat untuk mengumpulkan informasi penerbangan dan Aeoronotical Fixed Network (AFTN) yang mengolah semua data penerbangan . AFTN adalah sistem jaringan pada AMSC yang digunakan untuk komunikasi data penerbangan antara satu bandara dengan bandara lainnya dengan menggunakan address dari setiap bandara, baik di Indonesia maupun di negara lain di dunia. Juga Bandung sendiri merupakan Subcentre Station yang memiliki address WICC.